Bacteriocin production by Lactobacillus pentosus ST712BZ isolated from boza - Todorov,Svetoslav D. (Sociedade Brasileira de Microbiologia, 2007)
Bacteriocin ST712BZ (14.0kDa in size) inhibits the growth of Lactobacillus casei,Escherichia coli, Pseudomonas aeruginosa,Enterococcus faecalis, Klebsiella pneumoniae and Lactobacillus curvatus. Growth of strain ST712BZ in BHI, M17, soy milk and molasses was similar to growth in MRS, with optimal bacteriocin production (12800AU/mL) recorded in MRS after 24h. The same level of bacteriocin production (12800AU/mL) was recorded in MRS broth with an initial pH of 6.5, 6.0 and 5.5. However, MRS broth (pH 6.5) supplemented with 1mM EDTA, yielded only 6400AU/mL. Low levels of bacteriocin activity were recorded in MRS broth with an initial pH of 5.0 and 4.5. Of all media compositions tested, MRS supplemented with tryptone (20.0g/L), glucose (20.0 to 40.0g/L), mannose (20.0g/L), vitamin B12, or vitamin C yielded 12800AU/mL. Glycerol concentrations of 1.0g/L and higher repressed bacteriocin production. Maximal bacteriocin activity (25600AU/mL) was recorded in MRS supplemented with Vit. B1 or DL-6,8-thioctic acid.